Pengembangan Lembar Kerja Peserta Didik (LKPD) pada Materi Teks Fabel Berbasis Saintifik - Hasanah, Uswatun (STKIP PGRI Bandar Lampung, 2024)
The purpose of this study was to identify what teachers and students need in learning to write scientific-based fable texts, develop teaching materials for Student Worksheets (LKPD) on scientific-based fable text material, and explain the results of expert validation of LKPD. This development research uses a modification of the Dick, Carey, and Carey development model, as well as Jolly & Bolitho. Grade VIII students and Indonesian language teachers are the subjects of this study. Data collection was carried out through a questionnaire. Based on the results of validation by practitioners or colleagues at Al-Azhar Middle School on aspects of learning design, operations, and visual communication, it is marked with an average score of 54 and an average percentage of 98.3% with a very feasible category. The results of validation by practitioners or colleagues at Al-Kausar Middle School on aspects of learning design, operations, and visual communication are marked with an average score of 59 and an average percentage of 98.3% with a very feasible category.